The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1007/s10072-017-3038-y
|View full text |Cite
|
Sign up to set email alerts
|

Brainstem reflexes are hyperactive in patients with drug-induced akathisia

Abstract: Akathisia is a sensori-motor phenomenon which is generally encountered as an adverse effect of antidopaminergic medications suggesting involvement of dopaminergic pathways. We recently showed nociceptive flexor reflex was altered in akathisia as compared to restless legs syndrome and therefore, these findings may indicate co-involvement of pathways other than dopaminergic ones. To examine functional status of different pathways, we investigated auditory startle reflex (ASR), startle response to somatosensory i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…63 For example, DRBA-A may result from an intrinsic homeostatic response to the depletion of dopaminergic activity in the ventral striatum portion of the brain. 64 The nucleus accumbens is an area specifically implicated in the pathophysiology of akathisia due to its importance for reward and movement. It is theorized that compensatory overstimulation of this region may result in "senseless" behaviors and feelings of dysphoria observed with akathisia.…”
Section: Current Understanding Of Pathophysiologymentioning
confidence: 99%
“…63 For example, DRBA-A may result from an intrinsic homeostatic response to the depletion of dopaminergic activity in the ventral striatum portion of the brain. 64 The nucleus accumbens is an area specifically implicated in the pathophysiology of akathisia due to its importance for reward and movement. It is theorized that compensatory overstimulation of this region may result in "senseless" behaviors and feelings of dysphoria observed with akathisia.…”
Section: Current Understanding Of Pathophysiologymentioning
confidence: 99%
“…Whereas we found that spontaneous EPS is associated with treatment-emergent Akathisia, prior studies implementing a longer term follow-up of up to 24 months have demonstrated this relationship for treatment-emergent dyskinesia ( 13 ). Compared with dyskinesia, akathisia is an earlier onset antipsychotic induced EPS ( 30 ). We have implemented a short-term (3-months) follow-up in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Thirty-two studies evaluated TCR or TSR long-latency responses. Trigeminocervical reflex and TSR were assessed by stimulation of the supraorbital nerve in 17 studies, 1,3,5,11,12,18,21,26,31,34,[36][37][38][39][41][42][43] infraorbital nerve in 14 studies, 1,2,4,5,9,10,[15][16][17]19,20,22,25,36 mental nerve in four studies, 5,32,33,36 and masseteric nerve in one study. 40 Stimulation parameters, feasibility in healthy participants, and topographic distribution of long-latency TCR and TSR recordings with electrical single-pulse stimulation of the supraorbital, infraorbital, and mental nerves are summarized in Table 2.…”
Section: Long-latency Responsesmentioning
confidence: 99%